Wireless Health 2010 2010
DOI: 10.1145/1921081.1921103
|View full text |Cite
|
Sign up to set email alerts
|

Mobile healthcare in the US army

Abstract: The U.S. Army is exploring the use of mobile devices within the military healthcare system. To date, the Army has implemented programs that employ personal cell phones to remind patients of appointments, to disseminate health and wellness information, and to gather important information from patients that can alert clinicians, in real time, of their status. In addition, at the Walter Reed Army Medical Center (WRAMC), cell phones are being studied as an aid in diabetes management. These programs have been succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There are also a number of research achievements in military applications of BBNs. At Walter Reed Army Medical Center (WRAMC), research on supplementary treatments involving cell phones as tools for diabetes treatment was conducted [ 11 ], and this could have a profound impact on the outcome of remedies for the elderly and patients with diabetes or other chronic diseases by introducing WBANs in remote health monitoring. Emeka E. Egbogah et al proposed a cost-efficient data transmission method to meet the demands of monitoring soldiers’ vital signs [ 12 ].…”
Section: Related Workmentioning
confidence: 99%
“…There are also a number of research achievements in military applications of BBNs. At Walter Reed Army Medical Center (WRAMC), research on supplementary treatments involving cell phones as tools for diabetes treatment was conducted [ 11 ], and this could have a profound impact on the outcome of remedies for the elderly and patients with diabetes or other chronic diseases by introducing WBANs in remote health monitoring. Emeka E. Egbogah et al proposed a cost-efficient data transmission method to meet the demands of monitoring soldiers’ vital signs [ 12 ].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have been conducted to evaluate the effectiveness of mobile phones for assisting with diabetes self-management [2,9], and some standards are emerging with regard to how to design mobile applications in general [10], as well as mobile medical applications in particular [11], but research about the usability evaluation of applications for mobile devices is still a relatively new area [12]. A comprehensive survey of the status and trends of 200 mobile-health applications was conducted in [13] but it differs from the work presented here in a number of ways: it considered a broader range of healthcare applications, it was based on the user perspective rather than that of experts and it was restricted solely to the iOS platform.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Over a 12-week period, a control group and a group using the video cell reminder system were studied to see if blood glycemic levels could be adequately monitored by the system. The study revealed blood glucose levels were significantly lower in individuals who were not reminded to check their blood glucose levels versus those who were reminded (Poropatich et al, 2010).…”
Section: M-health Apps For Clientsmentioning
confidence: 89%
“…Mobile device apps are helping to bridge this gap by providing phone reminders for taking medication and following home-based therapeutic programs. In a study conducted by Poropatich et al (2010), a video cell phone reminder system was implemented to improve glycemic control in U.S. Army diabetic patients. Over a 12-week period, a control group and a group using the video cell reminder system were studied to see if blood glycemic levels could be adequately monitored by the system.…”
Section: M-health Apps For Clientsmentioning
confidence: 99%